Case report on anorexia nervosa - Preeti Srinivasa (Indian Journal of Psychological Medicine, 2015)
Anorexia nervosa is an eating disorder characterized by excessive restriction on food intake and irrational fear of gaining weight, often accompanied by a distorted body self-perception. It is clinically diagnosed more frequently in females, with type and severity varying with each case. The current report is a case of a 25-year-old female, married for 5 years, educated up to 10 th standard, a homemaker, hailing from an upper social class Hindu (Marvadi) family, living with husband′s family in Urban Bangalore; presented to our tertiary care centre with complaints of gradual loss of weight, recurrent episodes of vomiting, from a period of two years, menstrual irregularities from 1 year and amenorrhea since 6 months, with a probable precipitating factor being husband′s critical comment on her weight. Diagnosis of atypical anorexia nervosa was made, with the body mass index (BMI) being 15.6. A multidisciplinary therapeutic approach was employed to facilitate remission. Through this case report the authors call for the attention of general practitioners and other medical practitioners to be aware of the symptomatology of eating disorders as most patients would overtly express somatic conditions similar to the reported case so as to facilitate early psychiatric intervention.